Transformation of University Models: Analysis of the Development Strategies of Universities in the World - D. A. Shtykhno; L. V. Konstantinova; N. N. Gagiev; E. A. Smirnova; O. D. Nikonova (Высшее образование в России)
The paper presents an analysis of the key characteristics of the typological models of modern universities and outlines the directions of their transformation. The concept of University 3.0 was used as a research methodology in view of the existing approaches to the classification of university models. The research method was the qualitative analysis of the strategic development documents of the various universities of the world posted on their websites. The selection of the universities for analysis was carried out on the basis of the results of the QS WUR 2022 ranking. The sample was made up of 30 universities from North America, Europe, Asia, and Russia, occupying various ranking positions. As a result, there were revealed the features of the strategic priorities for the development of Russian and foreign universities, as well as universities aimed at global and regional influence. A set of basic characteristics of typological models of universities 1.0-4.0 has been developed. It has been established that the transformation of these models takes place in the direction of increasing the scope of their mission, expanding the areas of activity, using new digital technologies, developing integration potential and strengthening the impact on society. The defining parameters for the formation of the model of the university of the future are focus on innovation and advanced continuous education, managed broad integration, diversification of income sources, social involvement and contribution to sustainable development. The presented complex of the main characteristics of typological models of universities can serve as a tool for assessing the compliance of a particular university with a particular model, as well as contribute to goal-setting in the development of the national higher education system and particular universities.